AMOBA: Innovation barriers of the millennial generation - Putra, Febrianur Ibnu Fitroh Sukono; Haziroh, Awanis Linati; Budiantoro, Risanda Alirastra; Lestari, Selvia Puji; Arsanda, Tiara Daffa (Master of Management, Department of Management, Faculty of Business and Economics Universitas Islam Indonesia, 2023)
The millennial generation is closely related to the Industrial Revolution 4.0, which focuses on digitalization and automation patterns in human life. There are six main barriers: usage perception barriers, perceived value barriers, risk barriers, tradition barriers, image barriers, and perceived cost barriers. Therefore, the role of universities is needed in encouraging the millennial generation to create more contemporary innovations. This study aims to analyze the negative impact of internal and external barriers that affect the low innovation of the millennial generation. The research method is quantitative exploratory, with a total sample of 274 respondents from various private universities in Semarang City. The sampling method used purposive sampling, and the data collection technique used a survey with a questionnaire designed in certain procedure. Analysis of research results using multiple linear regression, which in principle can address the hypothesis statistically and comprehensively. The results of this study are usage perception barriers, perceived value barriers, risk barriers, tradition barriers, image barriers, and perceived cost barriers have a negative significant effect on the low innovation level of the millennial generation. The importance of this research is to encourage university administrators to facilitate students to develop self-competence and create creative innovations.